Mindfulness, qigong and their impact on health - Oblitas, Luis A. (2018)
Mindfulness or full attention traces its origins to Tibetan Buddhism, and constitutes a form of meditation focused on breathing and a form of body scan which significantly impacts on the strengthening of health and the decreasing of disease symptoms. Qigong is an ancient Chinese system of Taoist origin that promotes health maintenance, healing and increase in vitality, based on respiration, posture and movement. In the West, more attention has been paid to the mindfulness tradition than to the qigong. Therefore, the purpose of this article is to demonstrate that the combination of both millenary techniques may have a greater impact on and benefit to health. They both correlate, base their techniques on meditation, and their combination may prove beneficial to reduce stress and promote well-being.